The Pesticide Question Environment, Economics, and Ethics - Pimentel, David.; Lehman, Hugh. (Springer US, 1993)
Pesticides have contributed impressively to our present-day agricultural productivity, but at the same time they are at the center of serious concerns about safety, health, and the environment. Increasingly, the public wonders whether the benefits of pesticides - `the perfect red apple' - outweigh the costs of environmental pollution, human illness, and the destruction of animals and our habitat. Scientists and government officials are suspected of promoting commercial interests rather than protecting human welfare.